Countywide implementation of crisis intervention teams: Multiple methods, measures and sustained outcomes. (5th October 2017) - Kubiak, Sheryl; Comartin, Erin; Milanovic, Edita; Bybee, Deborah; Tillander, Elizabeth; Rabaut, Celeste; Bisson, Heidi; Dunn, Lisa M.; Bouchard, Michael J.; Hill, Todd; Schneider, Steven
Abstract : The crisis intervention team (CIT) is a tool that can be used to foster pre‐booking diversion of individuals with mental illness from the criminal justice system and into community treatment services. Although CIT is often implemented solely as the training of law enforcement officers, the model stipulates that CIT is a vehicle for collaboration with community stakeholders who share a similar philosophy, as well as expanded mental health services offering a 24 hour–seven days per week drop‐off option for law enforcement officers. This case study presents the countywide implementation of CIT and expands previous findings on the prevalence of officer interaction with persons with mental health issues and CIT training outcomes, including changes in officer perception of individuals with mental health issues. Furthermore, analysis of the disposition of calls for officer assistance coded as mental health or suicide found significant increases in officer drop‐offs to the mental health crisis center post‐CIT training. Interrupted time series analysis determined that this change has been sustained over time, perhaps owing to the unique communication between county law enforcement and mental health staff. Implications for policy and practice are discussed.